Differential diagnosis of mucopolysaccharidosis and oligosaccharidosis of a sample of Egyptian children - Ekram Fateen; Manal Fouad Ismail; Noha Ahmed El-Boghdady; Mona Aglan; Mona Ibrahim; Amira Radwan (Faculty of Pharmacy, Cairo University, 2018)
Mucopolysaccharidosis (MPS) and oligosaccharidosis are lysosomal storage disorders (LSDs) that share many clinical features. The present study aimed to establish a protocol for the biochemical diagnosis of these disorders and their subtypes in affected Egyptian children as well as in pregnant females, in order to prepare children or fetus for enzyme replacement therapy. Urine, plasma and leukocyte samples were collected from 280 children with symptoms suggestive of LSDs. Fourteen amniotic fluid samples were collected from pregnant females having positive family history or having one affected sibling. Assessment of urinary glycosaminoglycans (GAGs) followed by two dimensional electrophoresis (2-DEP), thin layer chromatographic (TLC) for separation of oligosaccharides and plasma or leukocyte enzyme activity were performed. Six of pregnancies were diagnosed to have affected fetuses. 84 children had abnormal 2-DEP and classified as 26 MPS I, 10 MPS II, 24 MPS III and 24 MPS VI. Two were diagnosed as α-mannosidosis and 2 as GM1 gangliosidosis. In conclusion; MPS should be excluded before suspecting oligosaccharidosis. 2-DEP and TLC alone cannot rule out the diagnosis of either MPS or oligosaccharidosis and confirmation must be done by specific lysosomal enzymatic assay. Analysis of GAGs by 2-DEP in amniotic fluid can be promising method for prenatal diagnosis of MPS. Keywords: Mucopolysaccharidosis, Oligosaccharidosis, Two dimensional electrophoresis, Thin layer chromatography, Enzyme activity